2021
DOI: 10.1186/s43045-021-00138-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of burnout among interns in Riyadh, Saudi Arabia, and its relation to engaging in unethical behaviors

Abstract: Background Burnout is a work-related physical and/or emotional exhaustion among individuals working in the human service sector. This descriptive cross-sectional study aimed to estimate the prevalence of burnout among interns training in different hospitals in Riyadh, Saudi Arabia, and its relation to engaging in unethical behaviors. Results The study found a high burnout level in 135 (50%) of the interns with minimal overall engagement in unethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Our findings are supported by two other studies that concluded that burnout is a common issue among interns. 20 21 On the contrary, a study by Stanetic and Tesanovic 22 showed that older physicians with a higher length of service were exposed to more levels of stress and thus, a higher risk for burnout syndrome. Our study results might suggest that newly graduated medical personnel in Benghazi are having more difficulty dealing with their newfound responsibilities and adjusting to the workload of hospital life when compared to their colleagues with more work experience and higher degrees, which may be appropriated to poor managerial guidance, supervision, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by two other studies that concluded that burnout is a common issue among interns. 20 21 On the contrary, a study by Stanetic and Tesanovic 22 showed that older physicians with a higher length of service were exposed to more levels of stress and thus, a higher risk for burnout syndrome. Our study results might suggest that newly graduated medical personnel in Benghazi are having more difficulty dealing with their newfound responsibilities and adjusting to the workload of hospital life when compared to their colleagues with more work experience and higher degrees, which may be appropriated to poor managerial guidance, supervision, and lack of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, estos resultados son significativos en los contextos médicos, dado que se ha determinado que el burnout se asocia con un aumento de eventos adversos que reducen la seguridad del paciente (Al-Bsheish et al, 2022). Además, se ha señalado que existe una alta prevalencia de burnout entre los internos (50%) y que esta se asociación significativa entre el burnout relacionado con el paciente y la participación en comportamientos poco éticos (Ali et al, (2021), aunque en el presente estudio no se evaluó los eventos desencadenes o consecuencias derivadas del pade-cimiento del burnout entre los profesionales encuestados, efectivamente al reducir su desempeño laboral existe una alta probabilidad que los trabajadores comentan errores importantes o incumplan sus principios éticos.…”
Section: Discussionunclassified